Dysfunctional Metacognitive Beliefs in Patients With Obsessive–Compulsive Disorder and Pattern of Their Changes Following a 3-Month Treatment - Kim, Shin Tae; Park, Chun Il; Kim, Hae Won; Jeon, Sumoa; Kang, Jee In; Kim, Se Joo (Frontiers in Psychiatry, 2021)
Introduction Metacognitions, are considered to be crucial factors for the development and maintenance of pathologic anxiety. The present case-control study aimed to examine how metacognitive beliefs are associated with the diagnostic status and subtypes of obsessive-compulsive disorder (OCD). In addition, we examined the pattern of changes in metacognitive beliefs after a 3-month pharmacological treatment in patients with OCD. Methods A total of 562 cases with OCD and 236 healthy controls were assessed with the metacognitions questionnaire (MCQ), and various measures of OC symptom severity. Multivariate analyses of variance (MANOVA) with covariates was conducted to explore the relationship between subdimensions of metacognitive beliefs and OCD disease status. In addition, for the OCD patients, Pearson’s correlation was performed between baseline MCQ subdimensions and Obsessive-compulsive Inventory-Revised-Korean subscales (OCIRK). Finally, in a subset of drug-free OCD patients (n=144), the MCQ was reassessed after 3-months of treatment and patterns of changes in subdimensions of the MCQ were examined. Results Patients with OCD scored significantly higher on the four dimensions of the MCQ. There were significant associations between all MCQ subdimensions and OCIRK subscales. In the repeated-measure MANOVA, a significant group (nonresponders vs. responders)-by-time interaction effect was found only for the negative beliefs about the uncontrollability and danger of worry (NB) subdimension (F = 10.75; η2 = 0.072; p=0.001). Conclusion The presence of dysfunctional metacognitive beliefs in OCD subjects and their association with OCD characteristics suggests that dysfunctional metacognitions may play a crucial role in the pathophysiology of OCD. Improvement of metacognitive beliefs in the NB dimension may be a clinically meaningful correlate of good treatment response in the pharmacological treatment of OCD.